KEBERLANGSUNGAN AGENSI KREDIT MIKRO DALAM MEMBANGUN PENIAGA KECIL : STUDI KASUS BAITUL MAL WAT-TAMWIL DI PROVINSI RIAU - Saib, Khaidir (Eko dan Bisnis: Riau Economic and Business Review, 2016)
One of the micro-finance agency, is Baitul Mal wat-Tamwil considered as Islamic micro finance agencies that can provide financial services to people with low income. Islamic micro finance agencies in the past have always shown considerable achievements in terms of quantity, the contribution of the absorption of labor power to the gross national income, so that efforts to empower communities through the development of its own capabilities and social and economic institutions that can reach and serve more communities business unit that can not be reached directly by the general banking or Islamic banking. Looking a t the development effort, it is necessary to network  better security, so that the existence of Baitul Mal wat-Tamwil increasingly powerful, healthy and sustainable. The methodology used in this study kuaalitatif approach. This study shows that there are some factors that affect the sustainability of the BMT Kemaheran Access Capital, Ability to resolve problems pembayaranbalik, strict control function, Employee Collaboration (teamwork), Willing and Challenges Facing obstacles and Supply of Human Resources.